Glutamate from nerve cells promotes perineural invasion in pancreatic cancer by regulating tumor glycolysis through HK2 mRNA-m6A modification. (January 2023) - Li, Fengjiao; He, Chong; Yao, Hanming; Zhao, Yue; Ye, Xijiu; Zhou, Shurui; Zou, Jinmao; Li, Yaqing; Li, Jiajia; Chen, Shaojie; Han, Fanghai; Huang, Kaihong; et al.
Abstract: Background: Perineural invasion (PNI) has a high incidence and poor prognosis in pancreatic ductal adenocarcinoma (PDAC). Our study aimed to identify the underlying molecular mechanism of PNI and propose effective intervention strategies. Methods: To observe PNI in vitro and in vivo, a Matrigel/ dorsal root ganglia (DRG) model and a murine sciatic nerve invasion model were respectively used. Magnetic resonance (MR) imaging and positron emission tomography/computed tomography (PET-CT) imaging were also used to evaluate tumor growth. Publicly available datasets and PDAC tissues were used to verify how the nerve cells regulate PDAC cells' PNI. Results: Our results showed that glutamate from nerve cells could cause calcium influx in PDAC cells via the N-methyl-d -aspartate receptor (NMDAR), subsequently activating the downstream Ca 2+ dependent protein kinase CaMKII/ERK-MAPK pathway and promoting the mRNA transcription of gene METTL3. Next, METTL3 upregulates the expression of hexokinase 2 (HK2) through N6-methyladenosine (m6A) modification in mRNA, enhances the PDAC cells' glycolysis, and promotes PNI. Furthermore, the IONPs-PEG-scFvCD44v6-scAbNMDAR2B nanoparticles dual targeting CD44 variant isoform 6 (CD44v6) and t NMDAR subunit 2B (NMDAR2B) on PDAC cells were synthesized and verified showing a satisfactory blocking effect on PNI. Conclusions: Here, we firstly provided evidence that glutamate from the nerve cells could upregulate the expression of HK2 through mRNA m6A modification via NMDAR2B and downstream Ca 2+ dependent CaMKII/ERK-MAPK pathway, enhance the glycolysis in PDAC cells, and ultimately promote PNI. In addition, the dual targeting nanoparticles we synthesized were verified to block PNI effectively in PDAC. Graphical Abstract: ga1